Influence of Conditions on Early Warning in Lowering Levels of Infant Mortality and Health Disorders - Purworusmiardi, Tubagus; Kamisutara, Made; Artaya, I Putu; Sukoco, Agus (Journal of Applied Science, Engineering, Technology, and Education, 2019)
The process of the development of the world of digital technology has affected many areas. One of the central areas experiences penetration of digitization technology is in the area of health. One of the influences that add to the health field is medium with a large number of emerging health applications that can be easily accessed via a smartphone or tablet device. For example, in developed countries currently, examination process health the ear or hearing children have can be done using your smartphone. Through this tool, the doctor can diagnose the infection and prepare the proper treatment for patients. Growing number of mobile applications in the health field will certainly ease the course of patient care. There are currently a lot of digital health applications. For that we researchers designed a program shaped application that can be run over the web and sms gateway, to monitor the health conditions of babies from a variety of disorders. The information disseminated through the web and sms gateway can be accessed easily by the mothers who are nurturing her baby, so that a mother will get the right information on how to care for a baby with healthy and avoid distractions endanger the health of infants. this application may be applied in health centers, posyandu, or hospital.